IDENTIFICATION OF CHITNOLYTIC BACTERIA AT MORAMO WATERFALL IN SUMBER SARI VILLAGE, SOUTH KONAWE DISTRICT - apriyanto; aulya, sultan; Sulistiawan, Elfina (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2024)
Chitinolytic bacteria are microorganisms capable of producing chitinase enzymes that can degrade chitin into N-acetylglucosamine. Chitinase enzyme has many benefits, especially in agriculture it can be used as a fungal biocontrol agent, while in the field of Health the crude extract of chitinase produced by Myrothecium verrucaria can be used to kill mosquito larvae by disrupting the exoskeleton structure of Aedes aegypty (Sembiring el al., 2021). This study aims to identify chitinolytic bacteria found in Moramo waterfall in Sumber Sari village, South Konawe district. The research method used is a descriptive experimental method. Sampling in this study was carried out at three locations of the Moramo waterfall. Isolation of bacteria from the three locations of the waterfall obtained three isolates of bacteria that grew on Nutrien Agar media. On microscopic observation, isolate T1 showed gram-negative bacteria in the form of bacilli, isolate T2 contained gram-negative bacteria with cocci shape and in isolate T3 there were bacteria in the form of gram-positive cocci. The results of the identification of chitinolytic bacteria in Moramo waterfall using the Vitek 2 Compact method showed that at location T1 there was Rhizobium radiobacter bacteria. at location T2 the bacterial species could not be detected by Vitek 2 Compact. Meanwhile at location T3 there was Staphylococcus vitulinus bacteria. The conclusion from the results of the study was that chitinolytic bacteria Rhizobium radiobacter and Staphylococcus vitulinus in Moramo waterfall.